PENGARUH KEPRIBADIAN EXTRAVERT TERHADAP PERILAKU KONTRAPRODUKTIF GURU SMA NEGERI DI KECAMATAN MATRAMAN JAKARTA TIMUR - Rhoma Iskandar (Sekolah Tinggi Manajemen IMMI Jakarta, 2018)
The purpose of this research is to obtain information about the influence of extravert personality and distributive justice on counterproductive behavior teachers. This study uses a quantitative approach. This research was carried out using a quantitative survey with path analysis applied in testing hypotheses. Members of 95 teachers from high schools in Matraman Regency as samples were selected by simple random sampling. This study concludes: (1) There are direct negative effects of extravert personality on counterproductive behavior (2) There are direct negative effects of distributive justice on counterproductive behavior (3) There is a direct positive effect of extravert personality on distributive justice (4) There is a direct negative effect from extravert personality to counterproductive behavior through distributive justice.